2019
DOI: 10.1186/s13075-019-1933-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of corticosteroid monotherapy, and TNF inhibitors with or without corticosteroid in patients with refractory entero-Behcet’s disease

Abstract: Background Tumor necrosis factor (TNF) inhibitors (TNF-i) are effective in the treatment of entero-Behcet’s disease (BD). However, there is no objective tool for assessment of disease activity in entero-BD; therefore, it is not easy to evaluate treatment effectiveness in the clinical setting. In addition, because corticosteroid (CS) is considered for standard therapy, the effectiveness of TNF-i without CS has not been well examined. In this retrospective study, the effectiveness of CS without TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
(12 reference statements)
2
17
0
Order By: Relevance
“…The postoperative use of azathioprine can reduce clinical relapse [ 34 ]. Anti-TNF agents can also improve the clinical course of intestinal BD compared with the use of corticosteroids [ 25 , 35 ]. Furthermore, emergent surgery and elevation of postoperative erythrocyte sedimentation rate were prognostic factors for re-operation within 6 months in intestinal BD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The postoperative use of azathioprine can reduce clinical relapse [ 34 ]. Anti-TNF agents can also improve the clinical course of intestinal BD compared with the use of corticosteroids [ 25 , 35 ]. Furthermore, emergent surgery and elevation of postoperative erythrocyte sedimentation rate were prognostic factors for re-operation within 6 months in intestinal BD [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study conducted by Sugimura et al [78] showed that TNF-inhibitor agents induced both clinical and endoscopic remission in patients with intestinal BD. A 2019 study conducted by Miyagawa et al [79] also found that when corticosteroids are used in combination with TNFinhibitor agents that there was a significantly increased ulcer healing rate on endoscopy which could be another option prior to moving onto 3rd line agents.…”
Section: Medical Managementmentioning
confidence: 99%
“…Currently, endpoints for treatment are not well established in regard to whether the goal should be to aim for ulcer healing on endoscopy or simply clinical remission. Studies have been conducted that show some correlation (albeit weak correlation) between endoscopic ulcer healing and clinical improvement [79]. Kinoshita et al [76] also proposed an endoscopic scoring system to attempt to predict postsurgical relapse in patients who had required surgery for their disease and found that there was a relationship between patients with endoscopic relapse and clinical relapse.…”
Section: Advancements/future Developmentsmentioning
confidence: 99%
“…All observational studies scored a low risk of bias, with the quality assessment in Miyagawa et al [59] scoring 7/9 and the other studies scoring 8/9. It should be noticed that the number of patients included is not taken into account in the quality assessment.…”
Section: Systematic Review Into Anti-tnf-α Treatmentmentioning
confidence: 99%
“…Miyagawa et al [59] compared the effectiveness of anti-TNF-α treatment with corticosteroids. Next to this, the additive value of corticosteroids to anti-TNF-α treatment was studied.…”
Section: Efficacy Of Treatmentmentioning
confidence: 99%